2020
DOI: 10.3390/met10121671
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Surface Integrity Parameters in Roller Burnishing of Ti6Al4V

Abstract: Burnishing is considered a super finishing process able to drastically increase surface quality in terms of hardness and roughness of the manufactured parts. Consequently, it is considered appealing for the performance enhancement of products where the surface quality plays a crucial role. However, when burnishing grade 5 titanium alloy, a quantitative relationship between process parameters and surface integrity is still missing. This work provides a deep analysis of the burnishing parameters and their influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…An overlap is created between the working surface of the tool and the surface of the workpiece to be formed, and thus the tensile residual stress in the post-cutting surface zone is converted to a favourable compressive residual stress. This is one of the most advantageous properties of this process as, in addition to hardening, it also contributes to increasing the lifetime of the machine element, since it improves the resistance of the material to fatigue [14][15][16][17][18][19][20][21][22]. This paper deals with the examination of these two characteristics: surface micro-hardness and residual stress.…”
Section: Applications Of Burnishing On External Cylindrical Surfacementioning
confidence: 99%
“…An overlap is created between the working surface of the tool and the surface of the workpiece to be formed, and thus the tensile residual stress in the post-cutting surface zone is converted to a favourable compressive residual stress. This is one of the most advantageous properties of this process as, in addition to hardening, it also contributes to increasing the lifetime of the machine element, since it improves the resistance of the material to fatigue [14][15][16][17][18][19][20][21][22]. This paper deals with the examination of these two characteristics: surface micro-hardness and residual stress.…”
Section: Applications Of Burnishing On External Cylindrical Surfacementioning
confidence: 99%
“…Burnishing studies of wrought titanium alloys showed that beyond machining parameters also lubricants may have significant effect to surface hardness, wear resistance and fatigue [15,16], roller burnishing experiments of Ti4Al4V show that significant improvement of surface roughness and hardness can be achieved even in cryogenic conditions [17].…”
Section: Introductionmentioning
confidence: 99%
“…Rotella et al 19 conducted a study to analyze the effects of process parameters on surface roughness, surface hardness, and wear rate of Ti-6Al-4V alloy in the roller burnishing method. The study involved a thorough statistical analysis.…”
Section: Introductionmentioning
confidence: 99%